The Effect of Rugby Drills on 7's Rugby Playing Skills - Hind Hind; Anggi Setia Lengkana; Dewi Susilawati (STKIP Muhammadiyah Kuningan, 2023)
Rugby is a contact sport that alternates fast attacks with submaximal intervals of exercises such as walking and jogging. Very complex, high-intensity training programs such as running and specific competitions such as tackles, mauls, rucks and scrums. The research design used a pre-experiment because this study used a sample of 20, and the control group was not randomly selected. This study used a one-group pretest-posttest design. Based on the results of the research and discussion that has been presented regarding the data on the effect of rugby drills training on playing skills, it can be concluded that there is a significant influence between the pre-test and post-test on exercises training on rugby 7's playing skills.